Does stopping a statin increase the short‐term risk of a cardiovascular event?. Issue 6 (June 2016) - Frazier, Winfred T.; Joseph, Matthew; Wilson, Stephen A.
Abstract : Evidence‐Based Answer : Discontinuation of HMG Co‐A reductase inhibitor (ie, statin) therapy in patients with recent (24 hours to 60 days) cardiovascular (CV) events increases the risk for recurrent myocardial infarction (MI), ischemic stroke, and death between 30 days and 12 months (SOR: B, consistent findings from a systematic review of cohort studies and individual cohort studies). These risks were not observed in patients with stable coronary heart disease (CHD) who discontinued statin therapy over 4 to 6 weeks (SOR: B, RCT).